Process of construction of an educational video about speech therapy care in amyotrophic lateral sclerosis (Research, Society and Development, 2022)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease of the central nervous system, causing atrophy and generalized muscle weakness, hindering the functions of chewing, swallowing, speech and voice. The speech therapist plays the role of guaranteeing the functionality of communication and food, facilitating the independence and autonomy of the patient, providing a better quality of life. To this end, we can use effective educational resources (ER) such as videos. Objective: To describe the process of construction of an ER in the form of an educational video on speech therapy care in ALS, based on the CTM3 Method. Methods: Descriptive research of the methodological study type. For its elaboration, we chose the CTM3 Method (Santos, 2019), where in this method, the RE needs to be composed of: C (Product design), T (theoretical reference) and M3 (methodological framework, which is based on the theories of Transactional Analysis, Multisensory Application and Neurolinguistics). Results: This educational video has a duration of 2min 56s, easy access on electronic devices, good assimilation of its content by presenting visual and sound elements, which refers to stimulating the senses (hearing, vision, smell, taste and touch). The video was validated by a committee composed of three ad hoc evaluators experienced in the field of Education, Communication and Technology at MEST/UNCISAL. Conclusion: This video, based on the CTM3 method, demonstrated that it is relevant as an educational resource for the target audience, as it was validated by a commission. The videos have the ability to attract the audience's attention due to the audiovisual and sensory resources, facilitating the understanding of the content.